2023
DOI: 10.3389/fcimb.2023.1149679
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome: A line of defense against tuberculosis development

Abstract: The tuberculosis (TB) burden remains a significant global public health concern, especially in less developed countries. While pulmonary tuberculosis (PTB) is the most common form of the disease, extrapulmonary tuberculosis, particularly intestinal TB (ITB), which is mostly secondary to PTB, is also a significant issue. With the development of sequencing technologies, recent studies have investigated the potential role of the gut microbiome in TB development. In this review, we summarized studies investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 113 publications
(205 reference statements)
0
6
0
Order By: Relevance
“…Figure 6 A illustrates the top 25 citation bursts, with 15 studies cited highly for a sustained period of five years. The article Induction of intestinal Th17 cells by segmented filamentous bacteria [ 19 ], which has the highest co-citation frequency and the highest citation burst (Strength = 20.38), was published in the journal Cell in 2009. It reports that microbial symbiotic regulatory pathways may offer new opportunities for enhancing mucosal immunity and treating autoimmune diseases, providing strong evidence and a solid foundation for the study of mucosal immunity and commensal microbiota.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 A illustrates the top 25 citation bursts, with 15 studies cited highly for a sustained period of five years. The article Induction of intestinal Th17 cells by segmented filamentous bacteria [ 19 ], which has the highest co-citation frequency and the highest citation burst (Strength = 20.38), was published in the journal Cell in 2009. It reports that microbial symbiotic regulatory pathways may offer new opportunities for enhancing mucosal immunity and treating autoimmune diseases, providing strong evidence and a solid foundation for the study of mucosal immunity and commensal microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…To be exact, the direct communicative actions of the body’s mucosa modulate the commensal microbiota and also exert systemic immunomodulatory effects through signaling pathways. It is widely known that the immune balance of the body could be modified with oral administration or intranasal inhalation of probiotics or prebiotics, or fecal transplantation of intestinal flora, for the treatment of various immune-related diseases throughout the body, such as inflammatory bowel disease [ 12 ], asthma [ 13 ], chronic obstructive pulmonary disease [ 14 , 15 ], influenza [ 16 ], COVID-19 [ 17 ], hepatitis B [ 18 ], tuberculosis [ 19 ], neuroinflammation-related depression, anxiety disorders [ 20 ], etc. Yet, the therapeutic use of prebiotics is limited because they are living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…SCFAs are transported into host cells and bind to G-protein coupled receptors (GPCR) on epithelial and immune cells and produce anti-inflammatory cytokines [31,37,58,59]. Butyrate, which can act in the lungs by increasing the phagocytic function of dendritic cells, has been associated with anti-inflammatory properties during Mtb infections by causing a decrease in the proinflammatory cytokines and inhibiting host response to the infection [60][61][62][63]. Butyrate may also be converted to Phenylbutyrate (PBA), which has a synergistic effect with vitamin D to inhibit Mtb growth [64].…”
Section: Short-chain Fatty Acids (Scfa)mentioning
confidence: 99%
“…Butyrate may also be converted to Phenylbutyrate (PBA), which has a synergistic effect with vitamin D to inhibit Mtb growth [64]. This synergistic relationship upregulates LL-37, an antimicrobial peptide that increases the autophagy and intracellular killing of Mtb in host macrophages [62,65,66]. A study by Koh et al hypothesizes the important regulatory role of SCFAs in T cell differentiation and function due to the high expression of SCFA receptors in immune cells; however, more research is required to determine the specific mechanism and role of SCFAs in TB therapy [59].…”
Section: Short-chain Fatty Acids (Scfa)mentioning
confidence: 99%
“…Crucially, the functional impact of the microbiota on host immunity, mediated through microbial metabolic output, is lacking. Thus, based on 16S rRNA sequencing, earlier studies reported gut dysbiosis and discussed the possible impact of the detected taxonomic changes on the host ( Hu et al., 2019 ; Shi et al., 2021 ; S. Wang et al., 2022 ; Yu et al., 2023 ). Such taxonomic descriptions are not enough to understand microbial function.…”
Section: Introductionmentioning
confidence: 99%